Veterinary anesthetic and monitoring equipment - Cooley, Kristen G.; Johnson, Rebecca A. (Rebecca Ann) (Hoboken, New Jersey John Wiley & Sons, 2018)
"Veterinary Anesthetic and Monitoring Equipment is the first veterinary-specific resource solely dedicated to anesthetic and monitoring equipment used in clinical practice.
• Offers a practical guide to anesthetic and monitoring equipment commonly used in veterinary medicine
• Provides clinically oriented guidance to troubleshooting problems that may occur
• Discusses general principles applicable to any equipment found in the practice
• Presents information associated with novel anesthetic equipment and monitors"
Includes bibliographical references and index.
Keywords: Veterinary anesthesia; Intraoperative monitoring; Anesthesiology -- instruments; Intraoperative monitoring -- instruments